The benthic sea-silk-thread displacement of a sessile bivalve, Pinctada imbricata radiata (Leach, 1819) in the Arabian-Persian Gulf - Bruno Welter Giraldes (6655352) (2019)
A number of molluscs within the Class Bivalvia are defined by their ability to secrete fine silk like threads known as byssus which are used to anchor themselves to solid substrates. With relatively few exceptions the majority of these species remain in a sedentary state throughout their life attached via their byssal threads. However, observations of adult Pinctada imbricata radiata pearl oysters made during this study revealed this species’ ability to implement active movement. Byssal threads were secreted in a sequence of attachment and detachment phases, which resulted in the active displacement of the oyster. The oyster was observed, in the laboratory over a 9 day period, travelling a distance of 28cm in a horizontal path. After horizontal displacement, a vertical climbing phase was observed until the oyster reached the water surface at which point the byssus was discarded and the animal dropped, drifting in accordance with water current intensity. It is possible that these adaptations of byssal use are a result of environmentally induced evolutionary change within P. i. radiata. Other Information Published in: PLOS ONE License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1371/journal.pone.0215865